Trends in the drowning mortality rate in Iran. Issue 4 (30th August 2019) - Derakhshan, Pegah; Saeedi Moghaddam, Sahar; Saadat, Soheil; Ghanbari, Ali; Rezaei, Nazila; Khosravi, Sepehr; Mehdipour, Parinaz; Amirmohammadi, Mina; Jahani, Shima; Sharif-Alhoseini, Mahdi; Jazayeri, Seyed Behzad; Chegini, Maryam; et al.
Abstract : Objective: The WHO estimates the global incidence of death by drowning to be about 300 000 cases per year. The objective of this study was to estimate the trend in mortality due to drowning in all provinces of Iran in all age groups and both genders from 1990 to 2015. Study design: The National and Subnational Burden of Diseases (NASBOD) project is a comprehensive project in Iran. It is based on the Global Burden of Disease study and includes novel methods to estimate the burden of diseases in Iran. Methods: This study used the results of the mortality rate due to drowning as part of NASBOD and investigated the causes behind the mortality rates. The data set recorded mortality rates by 19 age groups and two genders with the corresponding subnational pattern during the time period from 1990 to 2015. Results: The drowning mortality rate decreased in Iran from 1990 to 2015. From 1990 to 2015, the annual percentage change for males and females was −5.28% and −10.73%, respectively. There were 56 184 male and 21 589 female fatalities during the study period. The highest number of deaths was seen in 1993 with 4459, and the lowest number of fatalities was observed in 2015 with 903 deaths. Conclusion: Our data showed a decline in drowning mortality in Iran from 1990 to 2015, but the rates and declines varied by province. Our findings are of great importance to health officials and authorities in order to further reduce the burden of drowning.